UNLEASHING AGILE: Obstacles and Opportunities in Human Services. - LÓPEZ, RAFAEL; ROBINSON, DOUG (Policy & Practice (19426828), 2017)
The article discusses the study conducted by Accenture and the National Association of State Chief Information Officers regarding the value of agile development among chief information officers (CIOs). Tackled is the automation of business processes. Also explored is the evolution of Agile as a software development methodology.